2010
DOI: 10.2337/db09-1207
|View full text |Cite
|
Sign up to set email alerts
|

The Natural Protective Mechanism Against Hyperglycemia in Vascular Endothelial Cells

Abstract: OBJECTIVEVascular endothelial cells (VECs) downregulate their rate of glucose uptake in response to hyperglycemia by decreasing the expression of their typical glucose transporter GLUT-1. Hitherto, we discovered critical roles for the protein calreticulin and the arachidonic acid–metabolizing enzyme 12-lipoxygenase in this autoregulatory process. The hypothesis that 4-hydroxydodeca-(2E,6Z)-dienal (4-HDDE), the peroxidation product of 12-lipoxygenase, mediates this downregulatory mechanism by activating peroxis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
68
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(75 citation statements)
references
References 40 publications
3
68
4
Order By: Relevance
“…Being saturated, PA is not subjected to peroxidation, yet it effectively augmented 4-HNE production in INS-1E cells by increasing the availability of AA and LA to peroxidation. We, and others, have reported that 4-hydroxyalkenals activate the PPARδ nuclear receptor in various cells, including beta cells [13,19,24,35,38]. The findings that 4-HNE scavenging with L-carnosine and PPARδ inhibition or its silencing attenuated PA-induced GSIS further support the role of the 4-HNE-PPARδ axis in beta cell function [13,39].…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Being saturated, PA is not subjected to peroxidation, yet it effectively augmented 4-HNE production in INS-1E cells by increasing the availability of AA and LA to peroxidation. We, and others, have reported that 4-hydroxyalkenals activate the PPARδ nuclear receptor in various cells, including beta cells [13,19,24,35,38]. The findings that 4-HNE scavenging with L-carnosine and PPARδ inhibition or its silencing attenuated PA-induced GSIS further support the role of the 4-HNE-PPARδ axis in beta cell function [13,39].…”
Section: Discussionsupporting
confidence: 59%
“…PPARδ-luciferase reporter assay Subconfluent INS-1E cultures were co-transfected with the hPPARδ expression vector along with the hRXR-, green fluorescent protein (GFP)-and Renilla luciferase expression vectors and the 3XPPRE-TK-luciferase reporter, as described [19]. The yield of the transfection, assessed by GFP fluorescence, was >85%.…”
Section: Fatty Acid-based Lipidomic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The authors associate the findings to arachidonic acid metabolites, products of lipid peroxidation and calreticulin-induced destabilization of GLUT1 mRNA, rendering it susceptible to degradation. Consequently, the cell content of GLUT1 protein and its abundance at the PM are reduced, resulting in downregulation of glucose uptake (47). These studies seem to indicate an entirely different mechanism that involves ROS-induced lipid peroxidation and generation of a second messenger that activates peroxisome proliferator-activated receptor-␦.…”
Section: Discussionmentioning
confidence: 87%
“…The principles have mostly commonly been explored with linoleic acid and have focused on the formation of 4-hydroxy-2-nonenal (HNE), owing to the fact that it is one of the most abundantly formed lipid peroxidation products and has interesting biological effects [8,28,29]. The mechanisms are (i) reduction of hydroperoxide to an alkoxyl radical in the presence of a transition metal followed by β-scission; (ii) Hock rearrangement of a hydroperoxide and migration of a C-C to a C-O bond and cleavage; (iii) cyclization to form a dioxetane and subsequent cleavage.…”
Section: Aldehydes Are Fragmentation Products Of Oxidized Lipidsmentioning
confidence: 99%